The rarest cause of impaction of mandibular third molar - A case report - Chandresh Jaiswara; Alka Rani; Neeraj Kumar Dhiman (Elsevier, 2016)
Mandibular tooth impaction is a very common finding and is usually associated with so many local and systemic causes in which the pathway of tooth eruption is obstructed or misdirected. The local causes are either a local bony lesion or an abnormal position of the adjacent tooth. The case presented here is associated with a very rare cause of impaction, which is the hamartomatus growth of the first and second molars causing the obstruction and leading to the impaction of the adjacent third molar tooth.